(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of Artificial Intelligence has propelled the sporting industry far ahead of its time and will continue to do so. For the present circumstance, AI has had an inconceivable importance in the field of sports industry. It has made sure that the broad field of sports not only follows customs that has been passed down from generations but also improved on it, adapting it to the present circumstances of human development. This paper makes the investigation on the upside of AI sports industry. In this paper, we have used Minimax Algorithm to compute each game utility calculation form the game tree. The report begins by offering diagram direct with respect to how two viewpoints joins. It furthermore perceives a segment of the AI applications used in games today. The investigation finds that there are enormous fans who are the essential beneficiary of AI development jobs. Moreover associations is connected with sports are growing speedy on account of high care made through technology. The future will be all the surer because of the right changes in the right directions. Accordingly, it very well may be recommendable for sports associations to remain refreshed.